2015
DOI: 10.1039/c4fd00214h
|View full text |Cite
|
Sign up to set email alerts
|

Do solid-to-solid polymorphic transitions indl-norleucine proceed through nucleation?

Abstract: Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, the Library will make the material inaccessible and/or remove it from the website. Please Ask the Library: http://uba.uva.nl/en/contact, or a letter to: Library of the University of Amsterdam, Secretariat, Singel 425, 1012 WP Amsterdam, The Netherlands. You will be contacted as soon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 34 publications
3
25
0
Order By: Relevance
“…Indeed earlier molecular dynamics simulations 14 showed that the β ↔ I 2 transitions become less frequent with increasing simulation cell size. The present results which show linear isotropic scaling, triggered a reanalysis of these molecular dynamics simulations.…”
Section: Nudged Elastic Band Calculationsmentioning
confidence: 93%
See 2 more Smart Citations
“…Indeed earlier molecular dynamics simulations 14 showed that the β ↔ I 2 transitions become less frequent with increasing simulation cell size. The present results which show linear isotropic scaling, triggered a reanalysis of these molecular dynamics simulations.…”
Section: Nudged Elastic Band Calculationsmentioning
confidence: 93%
“…This is in accordance with experimental thermal stage microscopic observation where in some cases the crystal is found to "wobble" during the transition, but the cell parameters before and after the transition are again the same. 14,21 The dashed line in Fig. 5 shows the fit with only the prefactor as a free parameter and .…”
Section: Nudged Elastic Band Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the possible phase changes between different polymorphic forms of the same crystalline drugs is critical because different forms can have radically different behavior during dissolution, storage, and manufacturing. The transition between the β and α forms of DL-norleucine is a typical example of a solid-solid phase change simulated with MD [438]. It was possible to discover different transition pathways and their energy barriers and to determine that the transition proceeded by cooperative movement between the bilayers in the crystal.…”
Section: Studies Of Crystalline and Amorphous Solidsmentioning
confidence: 99%
“…I will present advanced Molecular Dynamics (MD) simulations of two enantiotropically related polymorphic forms of DL-norleucine: α (room temperature) and β (low temperature), which are thought to transform through a martensitic mechansism by sliding along two cell axes. I will show that the mechanism of the transition occurs through a cooperative movement of bilayers via an intermediate state [1,2]. Although the layers move in a concerted fashion, the results further indicate that local fluctuations in the conformations of the aliphatic chains play a crucial role in keeping the cooperative mechanism sustainable at large length scales (see figure).…”
mentioning
confidence: 99%